TAHAPAN-TAHAPAN REKRUTMEN CALON ANGGOTA DPRD KABUPATEN KAMPAR DARI PKS PADA PEMILIHAN UMUM TAHUN 2019 DI KABUPATEN KAMPAR - Humairoh Khairani; Adlin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Regency council member come from political parties which are elected trouugh the eletion. as the legislature regency parliament has a major role on the implementation of regional autonomy. As one political party, the PKS Kampar Regency participating in the 2019 election in Kampar Regency can be said to be successful because it was able to significantly increase the number of votes acquired and pass 5 people recruited as legislative candidates from the quota of 45 seats for members of the Kampar Regency DPRD. This was assessed because of the success of political recruitment carried out by PKS. So that this study aims to look at the stages of recruitment of legislative candidates carried out by the PKS DPD in the 2019 elections in Kampar Regency. This research is descriptive research approach with several informants selected using purposive sampling technique. The location of this research was conducted in Kampar Regency. The data collection techniques carried out are through interviews and documentation. The data analysis technique used is an interactive analysis model, namely data collection, data reduction, data presentation, and drawing conclusions or verification. These results of the study concluded that based on the observations and analysis of the researcher is 1). The stages of recruiting candidates for legislative members from PKS in the 2019 general elections in Kampar Regency are as follows: a). The preparation stage, Kampar Regency PKS was able to form 21 PKS DPC management at the sub-district level. b). At the screening (certification) stage, PKS did not put forward any special requirements, but registration information was distributed privately to each DPC so that only party members knew. Then the external party was proposed by the DPC. Then PKS can be said to use closed recruitment. C). At the nomination stage, PKS formed a winning team for the Prosperous Justice Party (PKS) election chaired by Tamarudin, S.Pd.I. d). At the election stage, the results of the Prosperous Justice Party (PKS) DPD in Kampar Regency were ratified without any changes by the Prosperous Justice Party (PKS) Riau Province DPW. 2). Factors influencing the recruitment of Prosperous Justice Party (PKS) legislative candidates can be concluded, among others, due to the effects of the presidential and vice-presidential elections or the presidential election effect and the way the PKS DPD recruits potential legislative candidates and qualified regeneration. Keywords : Recruitmen, Member of Regency Parliament, PKS